Redescription of Clubiona gongi Zhang, Yin, Bao & Kim, 1997 (Araneae: Clubionidae) with the first description of the male - Yang, Daxing; Zhou, Guchun; Yang, Maofa; Peng, Xianjin (Zootaxa, 2019)
Clubiona Latreille, 1804 comprises 503 species across the world, of which 122 species were reported from China. Nearly one-third of Chinese species have been described with single-sex (World Spider Catalog, 2018). Twenty-eight species have been reported from Guizhou Province (Wang et al. 2015; Wu et al. 2015; Li & Lin 2016; Yu et al. 2017; Wang et al. 2018; Zhang et al. 2018).